Edukasi Nilai Good Citizen Guna Mewujudkan Demokrasi dan Integrasi Nasional di SMA Kemala Bhayangkari Kubu Raya - Hardi Alunaza (I-Com: Indonesian Community Journal, 2024)
This service community is based on the many problems faced by today's young generation which are influenced by globalization. In this case, the process of educating the value of good citizenship is important so that the younger generation avoids the negative impacts of globalization. The good citizen values ​​intended in this service community focus on three important things, namely good intelligence, good responsibility and good attitude.These three things will encourage the formation of a young generation who can support the creation of better democracy and national integration in Indonesia. This also supports community participation in the state administration process by working together and respecting each other.This activity was carried out in November 2023 by providing outreach using socialization and education methods, questions and answers and discussions related to instilling the values ​​of good citizenship which have an influence on the formation of a better democracy in Indonesia. After participating in the activity, students became more aware of equal rights and guarantees of justice for every citizen by prioritizing multiculturalism, as well as factors inhibiting good citizenship which have an impact on social inequality and nation development.